2003
DOI: 10.1046/j.1365-3083.2003.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Host Immune Responses by Overexpression of Immunodominant Antigens of Mycobacterium tuberculosis in Bacille Calmette–Guérin

Abstract: Based on their immunodominant nature and ability to induce appropriate immune responses in the host, several antigens of Mycobacterium tuberculosis have shown promise of protection. However, most of the candidate vaccines developed by employing various strategies have afforded protection that is at best comparable with bacillus Calmette-Guérin (BCG) in animal models. Due to the inherent ability of BCG to prime cellular responses in the host, it has become an attractive vehicle for development of a vaccine agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
0
24
1
Order By: Relevance
“…BCG antigen stimulated splenocytes from non-immunized mice (38 +/− 17 pg/mL) had similar level of IL-1β compared to mice immunized with BCG/ lactoferrin (44 +/− 21 pg/mL); production of IL-1β was significantly decreased in splenocytes from the BCG immunized group (24 +/− 13 pg/mL) compared to the BCG/lactoferrin group. TB vaccines are useful when given as a one time injection or when administered using various schedules of prime-boost protocols [10,14,15,[43][44][45][46][47][48][49]. The next experiments examined the BCG/lactoferrin saline immunization protocol to generate protection against MTB infection when mice were immunized once (Protocol C), or when boosted prior to infection (Protocol D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCG antigen stimulated splenocytes from non-immunized mice (38 +/− 17 pg/mL) had similar level of IL-1β compared to mice immunized with BCG/ lactoferrin (44 +/− 21 pg/mL); production of IL-1β was significantly decreased in splenocytes from the BCG immunized group (24 +/− 13 pg/mL) compared to the BCG/lactoferrin group. TB vaccines are useful when given as a one time injection or when administered using various schedules of prime-boost protocols [10,14,15,[43][44][45][46][47][48][49]. The next experiments examined the BCG/lactoferrin saline immunization protocol to generate protection against MTB infection when mice were immunized once (Protocol C), or when boosted prior to infection (Protocol D).…”
Section: Resultsmentioning
confidence: 99%
“…Many novel vaccine candidates demonstrating superiority over the existing BCG vaccine are genetically modified live BCG recombinants [7,9,10,15,44,47,48], with a general realization of the requirement to maintain the multitude of cross-reactive mycobacterial antigens. In these studies, bovine lactoferrin was used to significantly enhance the current BCG vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-characterized lipoprotein vaccine antigens of Neisseria discussed above, bacterial lipoproteins have been shown to affect both the innate and acquired immune systems via such mechanisms as TLR2 signaling and the generation of cytotoxic T lymphocytes and bactericidal antibodies (11,104,204). As such, a number of lipoproteins from many pathogens have been evaluated as vaccine candidates (6,48,99,136,143,152,193). Many of these, however, have been administered in recombinant form, making it difficult to ascertain the contribution of the native acyl moiety to protection.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no empirical evidence to suggest it is a problem in human disease, the presence of the 19-kDa gene-and other possibly antiprotective proteins-in live mycobacterial vaccines remains a concern. At the very least, such proteins are of dubious value as vaccine candidates (127,191). Taken in total, these studies indicate that M. tuberculosis is able to interfere with almost every stage of the host's immune response (Fig.…”
Section: Interaction Of M Tuberculosis and The Host Immune Systemmentioning
confidence: 92%
“…The improved efficacy of rBCG30 came as something of a surprise, since BCG possesses a functional gene for Ag85B. However, recent work has shown that overexpression of genes can alter the immune response to the antigens they encode (127), reminding us that the mere presence of a gene tells us little about its expression in vivo and that a gene's effects may be modulated by the presence or absence of other genes. The second piece of supporting evidence is the observation that new vaccines based on attenuation of Mycobacterium bovis (the parental strain of BCG) are both more virulent and give greater protective efficacy than BCG (34).…”
Section: Replacing Bcg (Priming Vaccines)mentioning
confidence: 99%